Yield of three newly developed mustard varieties as affected by irrigation at different growth stages (Research in Agriculture Livestock and Fisheries, 2015)
Efficient use of water is essential for sustainable crop production and achieving food security especially where water is a scarce resource. A study was conducted at a farmers field near Rahmatpur, Mymensingh, Bangladesh during November 2012 February 2013 to study the effect of irrigation on the yield and yield attributes of three newly developed mustard varieties, namely Binasarisha-7 (Brassica juncea L), Binasarisha-8 (Brassica juncea L), and Binasarisha-4 (Brassica napus L). The experimental soil was silty clay with a bulk density of 1.43 g cm-3. There were four irrigation treatments (T1: no irrigation; T2: irrigation at vegetative stage; T3: irrigation at flowering stage; T4: irrigation at vegetative and flowering stage), each replicated three times in a split plot design. Irrigation showed significant effect on the yield attributes of the mustard varieties. The highest yield of 1.43 t ha-1 (46% higher over control) was obtained in treatment T4 of variety Binasarisha-7. The lowest yield of 0.63 t ha-1 was obtained in treatment T1 (control) of variety Binasarisha-4. For producing seed yield Binasarisha-4 was the most responsive to the irrigation treatments (T2T4). In contrast, the yield differences among the stage-wise irrigation treatments (T2T4) were not statistically significant for Binasarisha-8. The highest water use efficiency of 0.48 t ha-1 cm-1 was obtained in treatment T1 and the lowest of 0.28 t ha-1 cm-1 was in treatment T4. For cultivation of the mustard varieties Binasarisha-4, Binasarisha-7 and Binasarisha-8 in this type of climate, irrigation at vegetative and flowering stage may be recommended to produce higher yield.Res. Agric., Livest. Fish.2(2): 197-206, August 2015